Synthesis and initial in vitro evaluation of olmutinib derivatives as prospective imaging probe for non-small cell lung cancer - Muammar Fawwaz; Kenji Mishiro; Arwansyah Arwansyah; Ryuichi Nishii; Kazuma Ogawa (BioImpacts, 2024)
Introduction: Imaging a non-small cell lung cancer (NSCLC) using radiolabeled tyrosine kinase inhibitors (TKIs) has attracted attention due to their unique interaction with the target epidermal growth factor receptor (EGFR). Olmutinib (OTB) is one of the third-generation EGFR TKIs, which selectively inhibit EGFR L858R/T790M mutation. In this study, we aim to estimate the interaction of the iodinated OTB (I-OTB)-receptor complex by molecular docking. Furthermore, we will synthesize the I-OTB and evaluate its activity toward EGFR L858R/T790M by in vitro cytotoxicity assay. Methods: A molecular docking simulation was carried out using an AutoDock Vina program package to estimate the interaction of the ligand-receptor complex. The I-OTB, N-{3-iodo-5-[(2-{[4-(4-methylpiperazin-1-yl)phenyl]aminothieno{3,2-d}pyrimidin-4-yl)oxy]phenyl} acrylamide, was synthesized by introducing an iodine atom in the phenyl group in the 3-aryloxyanilide structure. The half inhibitory concentration (IC50) was determined by employing a 2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H tetrazolium monosodium salt (WST-8) assay to evaluate the activity of I-OTB. Results: The docking study exhibited that I-OTB could take an interaction similar to that of the parent compound. We successfully synthesized I-OTB and confirmed its structure by instrumental analysis. The binding energy of OTB and I-OTB in complex with EGFR T790M are -8.7 and -7.9 kcal/mol, respectively. The cytotoxicity assay showed that I-OTB also has an affinity towards the EGFR L858R/T790M mutation with the IC50 10.49 ± 5.64 𝜇M compared to the EGFR wild type with the IC50 over than 10 𝜇M. Conclusion: The cytotoxicity effect of I-OTB was comparable to that of OTB. This result indicates that the iodine substituent in OTB did not alter the parent compound selectivity toward double mutations EGFR L858R/T790M. Therefore, I-OTB is prominent for radioiodination, and [123/124I]I-OTB may be a promising candidate for EGFR L858R/T790M mutation imaging.